Volume 4A: Dynamics, Vibration, and Control 2017
DOI: 10.1115/imece2017-71469
|View full text |Cite
|
Sign up to set email alerts
|

Control of a Head Stabilization System for Use in Robotic Disaster Response

Abstract: This paper systematically describes the design and validation of a feasible control scheme for a robotic head stabilization system. Over the past few decades there has been a growing need for robotic systems to perform human rescue operations in the event of natural or manmade disasters. Before autonomous or remotely controlled robotic victim extraction can be realized, support systems with the capability to secure the head of a trauma victim in a manner that does not exacerbate existing spinal injuries needs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The purpose of the design is to improve the robot's adaptability in a complex disaster scene. On the other hand, a very recently published work in [30,40] presents a casualty extraction robot design called semi-autonomous victim extraction robot (SAVER) [41,42]. This robot is equipped with two manipulator arms and a head support system.…”
Section: Related Workmentioning
confidence: 99%
“…The purpose of the design is to improve the robot's adaptability in a complex disaster scene. On the other hand, a very recently published work in [30,40] presents a casualty extraction robot design called semi-autonomous victim extraction robot (SAVER) [41,42]. This robot is equipped with two manipulator arms and a head support system.…”
Section: Related Workmentioning
confidence: 99%
“…As shown in Figure 3, even if the head is encountered closer to one of the foam blocks, it will stop and not exert any force until the second one makes contact with the head, and thereby securing it in place. The mechanical design as well as force control of the proposed head support system is explained in detail in references [21,22]. Detailed experimentations described in reference [22] showed that the incorporation of the linear actuator and the sliding differential pulley was both too slow and too large for practical implementation.…”
Section: Electro-mechanical Designmentioning
confidence: 99%
“…The mechanical design as well as force control of the proposed head support system is explained in detail in references [21,22]. Detailed experimentations described in reference [22] showed that the incorporation of the linear actuator and the sliding differential pulley was both too slow and too large for practical implementation. Thus, it was determined that future designs required a rotary motor as well as a more compressed form factor in order to provide a workable design.…”
Section: Electro-mechanical Designmentioning
confidence: 99%
See 1 more Smart Citation
“…With an extensive sensor suite providing real time visual and force feedback, the operator will be able to successfully manipulate the injured person into the right posture using the dual arm manipulation system. In addition a robotic head stabilization system that autonomously stabilizes the head and neck of a patient has been fully designed, built and tested to guarantee desired degree of performance [107].…”
Section: Novel Solutionmentioning
confidence: 99%